Penatalaksanaan Fisioterapi Post ORIF Fraktur Humerus 1/3 Distal Sinistra dengan Modalitas Infrared dan Terapi Latihan - Ruhen Arya Bujana; Maya Triyanita (Lembaga Pengembangan Kinerja Dosen, 2026)
A fracture is a break in bone continuity due to sudden and excessive force, either directly or indirectly. Humeral fractures can be categorized into proximal, shaft, and distal types. ORIF with screws is a surgical procedure involving the implantation of internal fixation in the fractured bone, which aims to maintain the alignment of bone fragments during the healing process. The use of screws in ORIF procedures can cause complications such as pain, muscle spasms, movement restrictions, and decreased muscle strength. Physiotherapy management that can be used in such cases includes infrared intervention and exercise therapy. This scientific paper is structured as a case study. It highlights a patient case and collects data through the physiotherapy process. The modalities used include infrared therapy and exercise therapy. After four intervention sessions involving infrared therapy and post-ORIF exercises for a distal third humeral fracture on the left side, the results included reduced pain, increased joint range of motion, increased muscle strength, and improved functional ability. Physiotherapy management with infrared modalities and exercise therapy consisting of forced active, free active, and resisted active exercises, was carried out over four sessions.